Characterization of the mitochondrial genome of Arge bella Wei & Du sp. nov. (Hymenoptera: Argidae) - Shiyu Du; Gengyun Niu; Tommi Nyman; Meicai Wei (PeerJ, 2018)
We describe Arge bella Wei & Du sp. nov., a large and beautiful species of Argidae from south China, and report its mitochondrial genome based on high-throughput sequencing data. We present the gene order, nucleotide composition of protein-coding genes (PCGs), and the secondary structures of RNA genes. The nearly complete mitochondrial genome of A. bella has a length of 15,576 bp and a typical set of 37 genes (22 tRNAs, 13 PCGs, and 2 rRNAs). Three tRNAs are rearranged in the A. bella mitochondrial genome as compared to the ancestral type in insects: trnM and trnQ are shuffled, while trnW is translocated from the trnW-trnC-trnY cluster to a location downstream of trnI. All PCGs are initiated by ATN codons, and terminated with TAA, TA or T as stop codons. All tRNAs have a typical cloverleaf secondary structure, except for trnS1. H821 of rrnS and H976 of rrnL are redundant. A phylogenetic analysis based on mitochondrial genome sequences of A. bella, 21 other symphytan species, two apocritan representatives, and four outgroup taxa supports the placement of Argidae as sister to the Pergidae within the symphytan superfamily Tenthredinoidea.